Mutations of the nACh Receptor M4 Helix Reveal Different Phenotypes in Different Expression Systems: Could Lipids be Responsible? - Mesoy, Susanne M.; Bridgland-Taylor, Matthew; Lummis, Sarah C. R. (Frontiers in Physiology, 2022)
The role of the outermost helix (M4) in the pentameric ligand-gated ion channel (pLGIC) family is currently not fully understood. It is known that M4 is important for receptor assembly, possibly via interactions with neighbouring M1 and M3 helices. M4 can also transmit information on the lipid content of the membrane to the gating mechanism, and it may form a link to the extracellular domain via the Cys-loop. Our previous work examining the alpha4beta2 nACh receptor M4 helix using HEK cells indicated M4 here is more sensitive to change than those of other pLGIC. Many of these other studies, however, were performed in Xenopus oocytes. Here we examine the 9 previously identified non-functional alpha4beta2 nACh receptor M4 mutant receptors using this system. The data reveal that 7 of these mutant receptors do function when expressed in oocytes, with only 2, the conserved Asp at the intracellular end of M4, and a Phe in the centre, having a similar phenotype (non-functional) in both HEK cells and oocytes. The oocyte data are more consistent with studies in other pLGIC, and demonstrate the importance of the expression system used. Of the many differences between these two expression systems, we suggest that the different lipid content of the plasma membrane is a possible candidate for explaining these discrepancie